2020
DOI: 10.1097/meg.0000000000001620
|View full text |Cite
|
Sign up to set email alerts
|

Is insertion of a plastic stent better and safer than epinephrine injection in post sphincterotomy bleeding?

Abstract: Objectives Epinephrine injection is the therapy of first choice in post sphincterotomy bleeding (PSB), but may not be efficient in all cases and can cause postprocedural myocardial infarction. Plastic stent insertion (PSI) may be a better treatment. The aim of this retrospective study was to compare epinephrine injection with PSI with respect to efficacy and safety. Methods Clinical success, number of reinterventions and hospital stays after therapy, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Recent studies showed that metal stent could treat post-ERCP bleeding by compression [34][35][36]. Plastic stent insertion could also be an effective, alternative option for post-ERCP bleeding in patients, shown in one previous study [37]. Thus, we tried to analyze if temporary biliary stent insertion during ERCP could prevent post-ERCP bleeding in our ESRD patients.…”
Section: Patient Characteristics Are Shown Inmentioning
confidence: 97%
“…Recent studies showed that metal stent could treat post-ERCP bleeding by compression [34][35][36]. Plastic stent insertion could also be an effective, alternative option for post-ERCP bleeding in patients, shown in one previous study [37]. Thus, we tried to analyze if temporary biliary stent insertion during ERCP could prevent post-ERCP bleeding in our ESRD patients.…”
Section: Patient Characteristics Are Shown Inmentioning
confidence: 97%